Implementation of Rural Area Development Based on the Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration - Muh Muhyi Tombinawam; Mutia Cherawati Thalib; Abdul Hamid Tome (Universitas Negeri Gorontalo, 2023)
This study aims to determine how the implementation of rural area development in Bone Bolango Regency is based on Ministerial Regulation Number 5 of 2016. The legal basis of the rural area development policy is Law Number 6 of 2014 concerning Villages. The law has the purpose and function of creating a strong, independent, peaceful, and democratic village that is used to regulate the development of rural areas. The results of this study are; 1). The implementation of rural area development in Bone Bolango Regency based on Ministerial Regulation Number 5 of 2016 can be carried out by forming a Coordination Team for Rural Area Development, planning the preparation of the development plan in question, and cooperation and determination of the village sarasan; 2). Obstacles in the implementation of rural area development in Bone Bolango Regency based on Ministerial Regulation Number 5 of 2016 are the lack of formation of a Rural Area Development Coordination Team (TKPKP), and the lack of maximum implementation of rural area development in Bone Bolango Regency